(untitled) (Namibian Journal of Linguistics, Literature and Communication Studies, 2025)
Dyslexia, a neurological learning disorder affecting one’s ability to read, write or speak, is the most common learning disability experienced by children and adults. Various researchers have reported on the high illiteracy rates amongst dyslexic adults in Zimbabwe, due to inadequacy of existing intervention programs. This research was conducted to explore the benefits of integrating assistive technological solutions with existing intervention programs, so as to alleviate some of the effects of dyslexia. Using Design Science Research Methodology (DSRM), a Shona Android mobile learning application for primary school learners with dyslexia was developed with the goal of fostering learning and helping children improve some of their fundamental skills, such as reading comprehension, orthographic coding and visual motor integration skills. The application helps teach orthography, grammar and phonology of the Shona language with the use of the alphabet and its character sounds, vowels, consonants and parts of the Shona speech such as nouns, verbs and adjectives. Both quantitative (questionnaires, observations) and qualitative (interviews) sampling techniques were used in the evaluation phase of DSRM to uncover significant information about learning outcomes and discover conclusive findings about the application. The research concludes that Assistive technological solutions hold promising prospects in learning for dyslexic learners.